Growth Analysis of Pearl Millet Genotypes Grown Under Different Management Practices - Petrus Ausiku Ausiku; John George Annandale; Martin Joachim Steyn; Andrew Sanewe (Agronomy)
Pearl millet is a cereal crop vital for food security in Africa and Asia. It is widely adapted for dual-purpose production, providing grain for human consumption and fodder for livestock, particularly during dry seasons. This study aimed to evaluate three dual-purpose pearl millet genotypes from Namibia and South Africa while exploring prospects for future production practices. Growth analysis is essential for quantitatively assessing crop growth, development, and production. A growth analysis study was conducted by collecting and evaluating weather data, water use efficiency, and crop growth parameters that are valuable for modelling, allowing for observing and quantifying strengths and weaknesses between varieties for food and fodder or as dual-purpose varieties. The analysis focused on water use, plant height, fractional radiation interception, panicle number, tiller number, flowering date, stem diameter, panicle length, dry matter distribution, harvest index, grain yield, and panicle diameter, under well-watered, supplementary irrigation, and rainfed conditions. The landrace achieved a higher yield under well-watered conditions than the hybrid and improved varieties. The hybrid pearl millet produced a greater fodder yield than the improved short variety in well-watered and water-limited treatments. The improved variety suits grain production, whereas the landrace and hybrid are more suitable for dual-purpose production. The landrace performed well in rainfed and irrigated situations across the three seasons. The landrace (Kantana) recorded the highest grain yield (1.01 kg m−2), followed by the hybrid (Agrigreen) (0.97 kg m−2), while the improved variety (Kangara) had the lowest grain yield (0.74 kg m−2).